Population structure, floral diversity, habitat geography, and conservation status of Himalayan horse chestnut (Aesculus indica) in western Himalayan moist temperate forest ecosystems of Kashmir region - Irfan, Urwa; Shaheen, Hamayun; Manzoor, Muhammad; Nasar, Sidra; Khan, Raja Waqar Ahmed; Gillani, Syed Waseem; Alrefaei, Abdulwahed Fahad; Attique, Arbaz; Kamal, Asif; Razak, Sarah Abdul; Riaz, Malik Talha (Frontiers in Forests and Global Change, 2025)
This study provides a comprehensive assessment of the population structure, floral diversity, habitat geography, phytosociology, threats, and conservation status of Aesculus indica in the western Himalayan region of Kashmir. This study was designed to investigate distribution patterns, community structure, floristic diversity, and phytosociological attributes of Aesculus indica forests, as well as evaluating the habitat geography of species by using GIS analysis. Primary vegetation data and geographic features were collected via systematic quadrat-based sampling from 14 sites in the moist temperate ecosystem of Kashmir, ranging in elevation from 1400 to 2800 m. Population structure analysis revealed an average density of 435.85 stems/ha for A. indica, with a significant variation ranging from 220 to 1100 stems/ha. The species exhibited a high basal cover of 356.33 cm, emphasizing its significant role in the canopy structure of Himalayan forests. The study identified A. indica as a keystone species supporting a diverse floral community comprised of 168 plant species from 51 families. Phytosociological investigations revealed A. indica to be the dominant species with the highest Importance Value Index (IVI) of 48.81, indicating its ecological significance in the temperate forest ecosystems. The species exhibited a preference for north-facing aspects and an altitudinal range of 1400-2800 m, which constitute the most suitable habitats for A. indica. However, the study identified significant anthropogenic disturbances, including deforestation, overgrazing, and forest land encroachment, as major threats to A. indica populations in the study area. The deforestation intensity averaged 135 stumps/ha, with some sites exceeding 300 stumps/ha, indicating unsustainable fuelwood consumption Formatted: Font: Italic patterns and habitat degradation. . It is recommended to formulate effective conservation measures such as promoting sustainable forest practices, controlling invasive species, restoring degraded habitats, controlled grazing practices, community-based conservation initiatives, and promoting alternative livelihoods that support local communities to ensure the preservation of A. indica populations as well as ecosystem health. Sustainable forest management practices, including selective logging, habitat restoration, and community-based conservation initiatives, should be implemented to mitigate the impacts of deforestation and climate change on A. indica populations.